TEMPO/NaClO2/NaOCl oxidation of arabinoxylans. (1st May 2021) - Pandeirada, Carolina O.; Merkx, Donny W.H.; Janssen, Hans-Gerd; Westphal, Yvonne; Schols, Henk A.
Graphical abstract: Highlights: TEMPO-oxidation of arabinoxylan with various TEMPO:NaClO2 :NaOCl systems was studied. TEMPO:NaClO2 :NaOCl (1.0:2.6:0.4) creates an ox-AX with high molecular weight. Arabinuronoxylans with a xylan substitution pattern resembling the parental AX. Abstract: TEMPO-oxidation of neutral polysaccharides has been used to obtain polyuronides displaying improved functional properties. Although arabinoxylans (AX) from different sources may yield polyuronides with diverse properties due to their variable arabinose (Ara f ) substitution patterns, information of the TEMPO-oxidation of AX on its structure remains scarce. We oxidized AX using various TEMPO:NaClO2 :NaOCl ratios. A TEMPO:NaClO2 :NaOCl ratio of 1.0:2.6:0.4 per mol of Ara gave an oxidized-AX with high molecular weight, minimal effect on xylose appearance, and comprising charged side chains. Although NMR analyses unveiled arabinuronic acid (AraA f ) as the only oxidation product in the oxidized-AX, accurate AraA quantification is still challenging. Linkage analysis showed that > 75 % of the β-(1→4)-xylan backbone remained single-substituted at position O -3 of Xyl similarly to native AX. TEMPO-oxidation of AX can be considered a promising approach to obtain arabinuronoxylans with a substitution pattern resembling its parental AX.